Staying Young At Heart: Autophagy and Adaptation to Cardiac Aging - Leon, Leonardo J. (J Mol Cell Cardiol, 2015)
Aging is a predominant risk factor for developing cardiovascular disease. Therefore, the cellular processes that contributes to aging are attractive targets for therapeutic interventions that can delay or prevent the development of age-related diseases. Our understanding of the underlying mechanisms that contribute to the decline in cell and tissue functions with age has greatly advanced over the past decade. Classical hallmarks of aging cells include increased levels of reactive oxygen species, DNA damage, accumulation of dysfunctional organelles, oxidized proteins and lipids. These all contribute to a progressive decline in the normal physiological function of the cell and to the onset of age-related conditions. A major cause of the aging process is progressive loss of cellular quality control. Autophagy is an important quality control pathway and is necessary to maintain cardiac homeostasis and to adapt to stress. A reduction in autophagy has been observed in a number of aging models and there is compelling evidence that enhanced autophagy delays aging and extents life span. Enhancing autophagy counteracts age-associated accumulation of protein aggregates and damaged organelles in cells. In this review, we discuss the functional role of autophagy in maintaining homeostasis in the heart, and how a decline is associated with accelerated cardiac aging. We will also evaluate therapeutic approaches being researched in an effort to maintain a healthy young heart.